Does biochemical profile of follicular fluid in women undergoing assisted reproduction vary between the right and left ovaries? - Özdamar, Özkan; Gün, İsmet; Satılmış Ertuğrul, Serkan; Özden, Okan; Sofuoğlu, Kenan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Follicular fluid (FF) provides a substantial micro-milieu for the development of the oocytes. Moreover, the content of FF may also reflect the circulating biochemical environment and the changes in blood serum. Despite the known embriyological and histological similarities between right and left ovaries, differences do exist between their venous drainage, anatomical relations and cyclical physiological changes. The difference between the two ovaries in the response to controlled hyperstimulatons (COH) in IVF regimens was later confirmed by recent studies. The aim of this study was to compare the biochemical differences between the FFs yielded from the right and left ovaries in patients undergoing standart IVF treatment. Methods: A prospective observational study was conducted through the unexplained infertility patients with the age between 23-39 years, body mass index (BMI) ≤28 kg/m2, FSH ≤10 mIU/mL. FFs aspirated from the right and the left ovary of the patients were assayed for estradiol, calcium, phosphorus, uric acid, urea, total protein, AST, ALT, glucose, sodium, potassium and creatinine. A total of 10 patients undergoing IVF treatments were included. Results: The investigated parameters were not significantly different between FFs yielded from the right and left ovaries. Conclusion: According to the results of our study, biochemical profile of the aspirated FFs does not significantly differ between the right and the left ovary and consequently, either right or left ovaries provide similar micro-environments to the developing oocytes.